Analysis of the Effects of Rainfall, Land Use Changes, and Amount of Water Usage on Groundwater Level Decreasing (Study in Gedebage) - Muhammad Hafidh Alhaq; Bakhtiar Abu Bakar; R. Didin Kusdian (TECHNO-SOCIO EKONOMIKA, 2020)
Sustainable urban development has been one of the main concerns for policy-makers. Increasing rate of population and urbanization have resulted in several socio-environmental impacts on people. Hence, water resources management in cities, as one of the most vital strategies, has become more complicated and challenging. In this study, the impact of precipitation, land-use changes, and amount of groundwater usageon groundwater level fluctuations was assessed. Using precipitation, remote sensing maps data from satellites, data of groundwater level, and land-use was extracted and processed by different formula and mapping tools. Gedebage Area in Bandung, Indonesia was selected as the case study location. The potential impacts of urban development in this city on groundwater resources were studied. The results suggest that from 2014 to 2018, Groundwater level decreasion was to increase simultaneously with run off discharge. Society perception confirmed that 95% is affected by precipitation, landuse change and amount of water usage at significance <0.05 while this change rate was more intense during previous decades and is predicted to be increased by 2030. Since relationship between precipitation, land-use change and amount of groundwater usage on groundwater level decreasion is undeniable, novel methodology of this stsudy can be employed for other fast-growing cities in Indonesia. DOI: https://doi.org/10.32897/techno.2019.13.1.4